Comparative Analysis of Theoretical Models for Digital Forensic Readiness (DFR) in Nigerian Banking - Chibuzor Akujobi; Francisa Ogwueleka; Gilbert Aimufua; Steven Bassey (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2026)
The increasing shift to digital banking in Nigeria has accelerated cyber fraud losses, prompting banks to adopt proactive forensic readiness measures. Recent industry reports show that Nigerian banks lost more than N300 billion ($833 million) in a single quarter of 2023, a 534% increase year-on-year. Digital Forensic Readiness (DFR) is a proactive cybersecurity strategy that ensures digital evidence is preserved and ready for analysis before a breach occurs. This paper reviews leading forensic readiness models, including Locard’s Exchange Principle, the Diamond Intrusion Model, and the NIST Risk Management Framework, and compares their applicability to Nigerian banking. We integrate these theories into a proposed DFR framework tailored for Nigeria’s banking sector, drawing on local and global studies. Key components of DFR (such as policies, technology, people, and legal compliance) are discussed with illustrations. Current challenges, notably reactive culture, evidentiary gaps, and regulatory compliance, are highlighted. Finally, best practices and a synthesis framework are presented to guide Nigerian banks toward a more resilient forensic posture.